1993
DOI: 10.1161/01.cir.88.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac troponin I. A marker with high specificity for cardiac injury.

Abstract: Elevations of cTnI are highly specific for myocardial injury. Use of cTnI should facilitate distinguishing whether elevations of MBCK are due to myocardial or skeletal muscle injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
526
2
28

Year Published

1998
1998
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,043 publications
(576 citation statements)
references
References 41 publications
20
526
2
28
Order By: Relevance
“…1: 1A8 ϭ 110.2 Ϯ 11.6 mg compared with IgG ϭ 140.0 Ϯ 11.0 mg, p Ͻ 0.01 and Expt. 2: 1A8 ϭ 113.6 Ϯ 2.8 mg compared with IgG ϭ 149.6 Ϯ 15.8 mg, p Ͻ 0.01; n ϭ 5 mice per group); however, no differences were noted in levels of cardiac troponin I, a marker of myocardial injury (29,30), in serum from neutropenic or control mice at day 7 postinfection (data not shown).…”
Section: Virus Replication and Spread In Neutropenic Mice Following Imentioning
confidence: 91%
“…1: 1A8 ϭ 110.2 Ϯ 11.6 mg compared with IgG ϭ 140.0 Ϯ 11.0 mg, p Ͻ 0.01 and Expt. 2: 1A8 ϭ 113.6 Ϯ 2.8 mg compared with IgG ϭ 149.6 Ϯ 15.8 mg, p Ͻ 0.01; n ϭ 5 mice per group); however, no differences were noted in levels of cardiac troponin I, a marker of myocardial injury (29,30), in serum from neutropenic or control mice at day 7 postinfection (data not shown).…”
Section: Virus Replication and Spread In Neutropenic Mice Following Imentioning
confidence: 91%
“…Myocardial necrosis is signified by increased level of cTn.Cardiac troponin I (cTnI), in particular, is not expressed by injured or regenerating skeletal muscle, and is, therefore, exquisitely specific for myocardial injury. 8 In general, cTnI and cTnT provide comparable information, except in renal failure, where cTnT is more likely to be elevated. 9 Troponin elevation after myocardial necrosis occurs within 2-3 hours, reaches its peak in 24 hours, and remains elevated for 1 to 2 weeks.…”
Section: Troponin Assessmentmentioning
confidence: 98%
“…[19][20][21][22][23][24][25][26][27][28][29] Cardiac troponin I also remains elevated longer, usually up to 10-14 days.20 Recently it has also been shown that cTnI is an important prognostic indicator in patients presenting with unstable angina, even when CK-MB is not e l e~a t e d . l~\~&~~ Our study supports that notion.…”
Section: Why Use Cardiac Troponin I?mentioning
confidence: 99%